The atlas of beauty : women of the world in 500 portraits - Noroc, Mihaela (Ten Speed Press, an imprint of Crown Publishing Group, a division of Penguin Random House LLC, 2017)
Noroc has journeyed through more than fifty countries to celebrate the diversity of this fascinating world. This volume contains photographs of five hundred women, from tribes, conservative communities, and modern cities. Most were struggling and working hard, and were facing discrimination as women. But through it all they were shining with dignity, strength, and beauty.